Interpretacja biblijnego opisu stworzenia świata w "Ad Autolycum" Teofila z Antiochii - Misiarczyk, Leszek (Vox Patrum, 2024)
In his analysis of the biblical description of the creation of the world in Genesis 1, Theophilus emphasizes at the starting point that God created everything that exists from nothing through his Logos, excluding as erroneous all theories about the eternal existence of matter. In the perspective of the creation of the world, God gave birth (ἐγέννησεν) to Logos and Wisdom primarily as a beginning (ἀρχή). In the beginning, God creates light that shows things ordered by Him. In the interpretation of individual days of creation, he uses typology, seeing in individual elements of the created world an announcement of future life and resurrection of man and the activities of Christian churches. Therefore, the first three days of creation are the type of the Holy Trinity, the Father, the Son-Logos and the Spirit-Wisdom, i.e. existence without light, and the fourth day is the type of man for whom God created the sun and the moon. Finally, he adds that man's sin has caused animals that were naturally good and gentle to become evil and poisonous, but as man returns to life κατὰ φύσιν, animals will also regain their original gentleness.